2018–2019 Florida Citrus Pest Management Guide: Huanglongbing (Citrus Greening) - Megan M. Dewdney; Michael E. Rogers; Ronald H. Brlansky (EDIS)
This 3-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. Written by M. M. Dewdney, M. E. Rogers, and R. H. Brlansky, and published by the Plant Pathology Department, May 2018.